Identification of a Novel Second-Generation Circulating Recombinant Form (CRF48_01B) in Malaysia: A Descendant of the Previously Identified CRF33_01B - Li, Yue; Tee, Kok Keng; Liao, Huanan; Hase, Saiki; Uenishi, Rie; Li, Xiao-Jie; Tsuchiura, Takayo; Yang, Rongge; Govindasamy, Sumathi; Yong, Yean Kong; Tan, Hong Yien; Pybus, Oliver G.; et al. (Lippincott, Williams & Wilkins, 2010)
A molecular epidemiological investigation conducted among injecting drug users in eastern Peninsular Malaysia in 2007 identified a cluster of sequences (n = 3) located outside any known HIV-1 genotype. Analyses of near full-length nucleotide sequences of these strains from individuals with no recognizable linkage revealed that they have an identical subtype structure comprised of CRF01_AE and subtype B', distinct from any known circulating recombinant forms (CRFs). This novel CRF, designated CRF48_01B, is closely related to CRF33_01B, previously identified in Kuala Lumpur. Phylogenetic analysis of multiple CRF48_01B genome regions showed that CRF48_01B forms a monophyletic cluster within CRF33_01B, suggesting that this new recombinant is very likely a descendant of CRF33_01B. CRF48_01B thus represents one of the first examples of a "second-generation" CRF, generated by additional crossover with pre-existing CRFs. Corroborating these results, Bayesian molecular clock analyses indicated that CRF48_01B emerged in ~2001, approximately ~8 years after the emergence of CRF33_01B.